Plastics Waste Management in Developing Country: The Case of Ecuador - Lazo, Miriam; Adrián, Estephany; López, Wilmer; Menéndez, Alanis; Naranjo-Silva, Sebastián; Rigail-Cedeño, Andrés (LACCEI, 2024)
Plastic waste is a global concern due to its influence on health, the environment, and economic development. Ecuador is in the line to reduce plastic waste, representing 11% of the urban waste generated. Ecuador is making several efforts to achieve a circular economy model that encourages plastic waste management, recycling, and reuse. This review outlines the current state of plastic waste management, legislation, the recycling industry, and research challenges in Ecuador. Although the current legal framework is explicit about incorporating recycled plastic in single-use products, the plastics industry has few options for quality recycled materials. Also, the present law includes "extended producer responsibility" for the plastics industry to be involved directly in the PET recycling process, which proved to have a successful application model. However, since waste separation is implemented in around 33% of the country, most recyclates end up in landfills. Still, plastic manufacturers are looking for ways to comply with the regulations and incorporate circular economy policies within their companies. Finally, local academic research has proven the feasibility of alternative methods of plastics recycling, such as polymer blends and natural agro-waste-reinforced recycled plastic composites to meet circular economy trends.